Annual Review of Nursing Research, 24 (2006) : Focus on Patient Safety. - Fitzpatrick, Joyce J. (Springer Pub. Co., 2006)
Designated a Doody's Core Title!. Supporting the urgent need for new patient safety guidelines and practices, Focus on Patient Safety, provides the most current and authoritative research and review to help decision makers develop new and much-needed standards and practices in nursing. With contributions from experts in the field, this new up-to-date reference focuses on key disciplines and topics that are critical to patient safety today including:.: Patient safety indicators.; Medication errors.; Falls and injury prevention.; Hospital-acquired infections.; Patient safety in acute-care units.